Radiolabeled Antibody Fragment for Preparation of (177Lu-DOTA)m-PAMAM G3.0-F(ab’)2 trastuzumab as a Radiopharmaceutical for Cancer Therapy - R.D. Haryuni; M. Ramli; T Triningsih; S Sutari (Atom Indonesia, 2017)
Several radiolabeled monoclonal antibodies (mAbs) have been used as radioimmunotherapy (RIT) agents for cancer therapy. The use of mAbs as RIT agents is due to their ability to carry effectors, in the form of radionuclides which emit alpha (α) particles, beta (β) particles, or auger electrons, and bind specifically to cancer expressed receptor. This paper reports the preparation of radiolabelled trastuzumab in form of (177Lu-DOTA)m-PAMAM G3-F(ab')2-trastuzumab, which will be expected as a potential RIT agent for therapy of breast cancer overexpressed human epidermal growth factor receptor 2 (HER2). Due to its reduced molecular weight, the use of F(ab')2-trastuzumab on the aforementioned RIT agent candidate is expected to reach its target much faster compared to the intact trastuzumab. Meanwhile, the role of PAMAM G3 is to increase the specific activity of the radiotherapeutic agent of Lu-177 due to the ability of its 32 –NH2 functional groups that are able to bind many DOTAs (£ 31) which in turn can bind a large number of 177Lu. The preparation was initiated by fragmentation of trastuzumab using pepsin enzyme in 0.02 M acetic acid buffer with a pH of 4.5 to produce F(ab')2-trastuzumab with a purity of 95 % after purification with PD-10 column. The F(ab')2-trastuzumab was then reacted with succinimidyl 4-(N-maleimidomethyl) cyclohexane-1-carboxylate (SMCC) to produce SMCC-F(ab')2-trastuzumab. The next reaction was to conjugate SMCC-F(ab')2-trastuzumab with DOTA-PAMAM G3.0-SH, which was prepared by reaction NHS-DOTA with PAMAM G3.0 and followed by reacting it with 2-iminothiolane to give (DOTA)m-PAMAM G3.0-F(ab')2-trastuzumab. Finally, the (DOTA)m-PAMAM G3.0-F(ab')2-trastuzumab was radiolabelled with 177Lu to produce (177Lu-DOTA)m-PAMAM G3.0-F(ab')2-trastuzumab, resulting in a radiochemical purity of 98 % after purification with PD-10 column.Received: 31 October 2015; Revised: 30 June 2016; Accepted: 25 September 2016